2019
DOI: 10.1177/0961203319857132
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers of lymphoma development in primary Sjögren syndrome

Abstract: Sjögren syndrome is a systemic autoimmune disease that principally affects women between the fourth and sixth decades of life who present with sicca symptomatology caused by dryness of the main mucosal surfaces. The clinical spectrum of Sjögren syndrome extends from dryness to systemic involvement. Since 1978, Sjögren syndrome has been closely associated with an enhanced risk of lymphoma, one of the most severe complications a patient may develop. Primary Sjögren syndrome patients have a 10–44-fold greater ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 92 publications
1
57
0
3
Order By: Relevance
“…100 Among Japanese RA patients, the comorbidity rate of secondary Sjögren syndrome was reported to be approximately 10%. 101 Although primary Sjögren syndrome patients are estimated to have a 10-44-fold higher risk of lymphoma, especially B cell lymphoma, than healthy individuals, 102 one large epidemiological study reported that secondary Sjögren syndrome yielded an even higher risk than the primary form. 103 On the other hand, several studies have reported a higher risk for patients with primary Sjögren syndrome.…”
Section: Concomitant Diseases Other Than Ramentioning
confidence: 99%
See 2 more Smart Citations
“…100 Among Japanese RA patients, the comorbidity rate of secondary Sjögren syndrome was reported to be approximately 10%. 101 Although primary Sjögren syndrome patients are estimated to have a 10-44-fold higher risk of lymphoma, especially B cell lymphoma, than healthy individuals, 102 one large epidemiological study reported that secondary Sjögren syndrome yielded an even higher risk than the primary form. 103 On the other hand, several studies have reported a higher risk for patients with primary Sjögren syndrome.…”
Section: Concomitant Diseases Other Than Ramentioning
confidence: 99%
“…104,105 As increased BAFF levels were reported to be associated with the risk of non-Hodgkin lymphoma in primary Sjögren syndrome, 106 the environment of chronic B cell stimulation may be associated with the risk of lymphoma development in Sjögren syndrome. 102 As the LPD developing in Sjögren syndrome is commonly low-grade B cell lymphoma, especially B-cell marginal zone lymphoma and mucosa-associated lymphoid tissue (MALT) lymphoma, which are not common in MTX-LPD, the environment of chronic B cell stimulation in concomitant Sjögren syndrome does not directly influence the pathogenesis of MTX-LPD, but it may indirectly influence MTX-LPD in RA patients.…”
Section: Concomitant Diseases Other Than Ramentioning
confidence: 99%
See 1 more Smart Citation
“…As of today, there are no certain biomarkers of developing lymphoma in the course of pSS. In the recent years, there have been attempts to develop models which would increase the sensitivity of early lymphoma diagnosis in the population of pSS patients [16,17]. Some symptoms such as palpable purpura, salivary gland enlargement, low C4, leukopenia, positive cryoglobulins, monoclonal gammopathy, disease duration and positive RF are considered risk factors [18].…”
Section: Discussionmentioning
confidence: 99%
“…These are distributed with 79% in the parotid glands, 18% in the submandibular glands, 2% in the minor salivary glands, and 1% in the sublingual glands (4). In the parotid gland, the most frequent types of lymphomas are extranodal marginal zone lymphoma (EMZL), follicular lymphoma (FL), and diffuse large B-cell lymphoma (DLBCL) (5), with EMZL being especially predominant in patients with Sjögren's syndrome (6). The detection of certain chromosomal translocations by fluorescence in situ hybridization (FISH) is used as a diagnostic tool and especially in EMZL genetic rearrangements vary in frequency according to the primary anatomical site of disease establishing a link between genetics and homing of malignant lymphocytes (7).…”
Section: Introductionmentioning
confidence: 99%